Exploring Climate Risk Effects on Financial Performance in Energy Sector - Kesuma, Muhammad Ramadhani; Henrika S., Margareth; Ariswati, Lusiana Desy; Widaryo, Chandika Mahendra; Irianto, Ellen D. Oktanti; Aini, Rohana Nur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the impact of the Climate Change Performance Index (CCPI) on the financial performance of energy firms in Indonesia and Malaysia, with capital structure as a moderating factor, using panel data analysis. Data from 62 publicly listed energy firms over 2019–2023 were analyzed through fixed effects, random effects, and diagnostic tests (Chow, Hausman, and Lagrange Multiplier). Results reveal that CCPI does not significantly affect return on assets (ROA) (coefficient = -0.0065, p = 0.837), and capital structure shows no moderating effect (p = 0.806). Firm size exhibits a near-significant impact (p = 0.058) in the random effects model. Multicollinearity and time-invariant variables limit cross-country and sectoral analyses. Findings underscore the ASEAN context, where evolving climate regulations temper financial impacts, with firm size emerging as a critical resilience factor. Future research with broader datasets is recommended to address methodological constraints.